Brain network topology and personality traits: A source level magnetoencephalographic study. Issue 5 (8th June 2022) - Troisi Lopez, Emahnuel; Colonnello, Valentina; Liparoti, Marianna; Castaldi, Mauro; Alivernini, Fabio; Russo, Paolo Maria; Sorrentino, Giuseppe; Lucidi, Fabio; Mandolesi, Laura; Sorrentino, Pierpaolo
Abstract : Personality neuroscience is focusing on the correlation between individual differences and the efficiency of large‐scale networks from the perspective of the brain as an interconnected network. A suitable technique to explore this relationship is the magnetoencephalography (MEG), but not many MEG studies are aimed at investigating topological properties correlated to personality traits. By using MEG, the present study aims to evaluate how individual differences described in Cloninger's psychobiological model are correlated with specific cerebral structures. Fifty healthy individuals (20 males, 30 females, mean age: 27.4 ± 4.8 years) underwent Temperament and Character Inventory examination and MEG recording during a resting state condition. High harm avoidance scores were associated with a reduced centrality of the left caudate nucleus and this negative correlation was maintained in females when we analyzed gender differences. Our data suggest that the caudate nucleus plays a key role in adaptive behavior and could be a critical node in insular salience network. The clear difference between males and females allows us to suggest that topological organization correlated to personality is highly dependent on gender. Our findings provide new insights to evaluate the mutual influences of topological and functional connectivity in neural communication efficiency and disruption as biomarkers of psychopathological traits.